210Po/210Pb Disequilibria and Its Estimate of Particulate Organic Carbon Export Around Prydz Bay, Antarctica - Hu, Huina; Liu, Xiao; Ren, Chunyan; Jia, Renming; Qiu, Yusheng; Zheng, Minfang; Chen, Min (Frontiers in Marine Science, 2021)
Due to the remoteness and difficulty of sampling, the 210Po and 210Pb data are scarce in the Southern Ocean. Here, the activity concentrations of 210Po and 210Pb around Prydz Bay in austral summer were determined to understand their spatial variation and evaluate the dynamics of particle organic matter (POM). The activity concentrations of dissolved 210Po (D210Po) and 210Pb (D210Pb) range from 0.47 to 3.20 Bq•m-3 and from 1.15 to 2.97 Bq•m-3, respectively, with the lower values in the shelf. The particulate 210Po (P210Po) and 210Pb (P210Pb) are lower in the open ocean and increase to the coastal waters, among which the Circumpolar Deep Water (CDW) is the lowest. The activity concentration of total 210Pb (T210Pb) ranges from 1.26 Bq•m-3 to 3.16 Bq•m-3, with a higher value in CDW, which is ascribed to radiogenic production from 226Ra and subsequent lateral transport. Occasionally a high value of T210Po occurs in deep water (> 3.00 Bq•m-3), which may be caused by the remineralization of POM. The disequilibria between T210Po and T210Pb appears throughout the water column at most stations. The average T210Po/T210Pb)A.R. in the euphotic zone is 0.66, reflecting the effect of strong particle scavenging. There is a good positive correlation between the solid-liquid ratio of 210Po and POC, while 210Pb does not, indicating that particulate organic matter regulates the biogeochemical cycle of 210Po around Prydz Bay. Based on the 210Po/210Pb disequilibria, the export flux of POC in the water column is estimated to be 0.8–31.9 mmol•m-2•d-1, with the higher values in the shelf.